Prevalence of Hypertension in Pregnancy at Dr. Muhammad Zyn General Hospital, Sampang, in 2024 - Muafiya, Muafiya; Ina Sadiati, Amelia; Amin, Yuski (Jurnal KESANS : Kesehatan dan Sains, 2025)
Hypertension in pregnancy remains a leading cause of maternal and fetal morbidity and mortality, particularly in developing countries. This study aims to determine the prevalence and determinant factors of hypertension in pregnancy at Dr. Muhammad Zyn Regional Hospital, Sampang, in the year 2024. A cross-sectional study design was employed, utilizing electronic medical records of pregnant women diagnosed with hypertension from January to December 2024. The variables analyzed included maternal age, body mass index (BMI), gestational age, type of antihypertensive therapy, postpartum visits, as well as the severity and reduction of hypertension. A total of 332 patients were included in the analysis. The majority were aged 20–35 years (60.8%) and had pregnancies beyond 37 weeks of gestation (72.0%). Most participants were categorized as obese (55.7%) with a mean BMI of 31.84 kg/m². Grade 2 hypertension was observed in 64.2% of cases, while 19.0% presented with hypertensive emergencies. Following treatment, 66.9% of patients achieved normal blood pressure levels. Magnesium sulfate was the most commonly administered therapy. Logistic regression analysis revealed that high BMI (OR: 1.073), high parity (OR: 1.733), and a history of hypertension (OR: 2.331) were significantly associated with hypertensive disorders in pregnancy. These findings underscore the critical importance of early detection and appropriate management in reducing the risk of hypertensive complications during pregnancy